Revealing simultaneous enrichment and degradation mechanism of organic molecules driven by TENG via in-situ SERS - Sheng Zhang; Ziyu Zhou; Zhaojuan Shi; Jinfei Mei; Changguo Xue; Cheng Xu; Yabo Zhu (iScience)
Summary: Self-powered degradation (SPD) driven by the triboelectric nanogenerator (TENG) has attracted significant attention. However, the effects of TENG on the migration of organic molecules have not been fully explored. Herein, a simultaneous enrichment and degradation mechanism of organic molecules around the electrode in the TENG electric field is proposed by in-situ surface enhancement of Raman scattering (SERS). In-situ SERS reveals that in the TENG electric field, the characteristic peaks intensity of organic molecules exhibits dynamic trend of “initial enhancement followed by attenuation.” In the early degradation stages, the enrichment of organic molecules around the electrode exceeds the degradation quantity. As the reaction progresses, the enrichment gradually decreases, and degradation becomes dominant, leading to SERS intensity reduction. This phenomenon differs significantly from the molecular migration in the DC electric field. This work reveals the unique migration mechanism of organic molecules in the TENG electric field and provides theoretical support for SPD applications.